Teaching of artistic expressions as artistic vehicle of educational intervention - Morgado, Elsa Maria Gabriel (2015)
This article aims at beginning anew the discussion on the cross-sectional presence of arts on education and on the importance of training and artistic creation in the educational context. The arts bring an inclusive point of view and allow for synergisms without ever losing sight of its ground substance. Arts allow for the intersection of two existences: Informative and aesthetic. As such, this article contemplates the relevance by virtue of being applicable to the matter at hand two differing scenarios (at the Universidade de Trás-os-Montes e Alto Douro) leading to differing outcomes: On the one hand, didactics or the activities of educating or instructing on one-dimensional artistic expressions and didactics on multidimensional integrated artistic expressions and, on the other hand, artistic project on educational intervention, that is, arts as a means or tool for imparting academic disciplines.